Intravenous Carbetocin to decrease blood loss during open myomectomy: a randomized placebo-controlled study - Sallam, Hany F.; Shady, Nahla W. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Uterine leiomyomas are benign tumors of the uterus, which represent the most common neoplasms in women of reproductive age, and have a lifetime incidence of approximately 70% in the general population. The objective of this study was to assess the effect of using a single pre-operative dose of IV 100 μg Carbetocin on intra-operative blood loss in abdominal myomectomy surgeries. Methods: In a randomized double-blind placebo-controlled trial, 86 women undergoing abdominal myomectomy for symptomatic uterine leiomyomas were randomly assigned to receive a single dose of pre-operative of IV 100 μg Carbetocin (n = 43) or placebo (n = 43) just before the operation. The primary outcome was intra-operative blood loss. Results: Intra-operative blood loss was significantly lower in those women randomized to receive IV Carbetocin versus the placebo group (714.19±186.27 ml versus 1033.49±140.9 ml), p = 0.0001 The incidence of blood transfusion was increased in placebo group (69.8%) compared with (18.6%) in Carbetocin group, (P = 0.0001). Also, there was a significant reduction in operative time in Carbetocin group (66.35%±10.18) compared with placebo group (95.95±9.16), (P = 0.0001). Conclusions: A single pre-operative dose of IV Carbetocin (100 μg) is a simple applicable method for reducing intra-operative blood loss and operative time in abdominal myomectomy.